Isolation and Identification of Dominant Bacteria From Black Soldier Fly Larvae (Hermetia illucens) Envisaging Practical Applications - Gorrens, Ellen; Van Moll, Laurence; Frooninckx, Lotte; De Smet, Jeroen; Van Campenhout, Leen (Frontiers in Microbiology, 2021)
This study aimed to establish a representative strain collection of dominant aerobic bacteria from black soldier fly larvae (Hermetia illucens, BSFL). The larvae were fed either chicken feed or fiber-rich substrates to obtain a collection of BSFL-associated microorganisms. Via an approach based on only considering the highest serial dilutions of BSFL extract (to select for the most abundant strains), a total of 172 bacteria were isolated. Identification of these isolates revealed that all bacteria belonged to either the Proteobacteria (66,3%), the Firmicutes (30,2%), the Bacteroidetes (2,9%) or the Actinobacteria (0,6%). Twelve genera were collected, with the most abundantly present ones (i.e. minimally present in at least three rearing cycles) being Enterococcus (29,1%), Escherichia (22,1%), Klebsiella (19,8%), Providencia (11,6%), Enterobacter (7,6%), and Morganella (4,1%). Our collection of dominant bacteria reflects largely the bacterial profiles of BSFL already described in literature with respect to the most important phyla and genera in the gut, but some differences can be noticed depending on substrate, biotic and abiotic factors. Furthermore, this bacterial collection will be the starting point to improve in vitro digestion models for BSFL, to develop mock communities and to find symbionts that can be added during rearing cycles to enhance the larval performances, after functional characterization of the isolates, for instance with respect to enzymatic potential.